Paralyzing and myotoxic effects of a recombinant bothropstoxin-1 (BthTX-I) on mouse neuromuscular preparations - Gallacci, M.; Oliveira, M. A.; Dal Pal-Silva, M.; Cavalcante, WLG; Spencer, P. J. (Elsevier B.V., 2006)
As a first step to investigate the structure-function relationship of bothropstoxin-1 (BthTX-1), a myotoxin from Bothrops jararacussu snake venom, Our group previously cloned a recombinant toxin (rBthTX-1) in Escherichia coli. The aim or this work was to characterize the biological activities of this rBthTX-1 (1.0 mu M) in both phrenic-diaphragm and extensor digitorum longus preparations in vitro, by means of myographic and morphologic techniques. Native BthTX-1 (1.0 mu M) was used as a standard. The influence of heparin (27.5 mu g/ml) upon the biological activities of both toxins was also investigated. rBthTX-1 had similar effects to the native toxin inducing blockage of both directly and indirectly evoked contractions in phrenic-diaphragm preparations, and muscle damage characterized by edema, round fibers, and cell areas devoid of myofibrils. Interestingly the paralyzing activity of rBthTX-1 was slightly more potent than the native toxin. Heparin prevented paralyzing and myotoxic effects of both the native and recombinant toxins. This work shows that rBthTX-1 was expressed in a fully active form, and presents a biological profile similar to the native toxin. (c) 2005 Elsevier GmbH All rights reserved.
Keywords: myotoxin; phospholipase A(2); muscle damage; ultrastructure